An appendix adenocarcinoma mimicking appendicitis. Issue 2 (28th March 2016) - Wang, Ho‐Li; Lin, Chen‐Kun; Lin, Chun‐Che
Summary: Cancer of the appendix is very rare and is typically found incidentally in approximately 1% of patients who received appendectomies. Most of appendiceal tumors are carcinoid, adenoma, and lymphoma. Adenocarcinoma of the appendix accounts for only 10% of all primary appendiceal cancers and the treatment remains controversial. In this article, we report a 67‐year‐old man who presented with symptoms of appendicitis that was diagnosed as adenocarcinoma of the appendix Stage II. The patient was treated with right hemicolectomy. To date he remains asymptomatic.